Representação, verdade e justificação no neopragmatismo de Richard Rorty - Thiago Lopes Decat (2005)
The main subject of this dissertation is the conception of truth in theneopragmatism of Richard Rorty. It investigates all the course of the development of this conception, since the initial appropriations of the truth conceptions of James and Dewey until the last developments of his long debate with Donald Davidson. This writer, being his most constant and important interlocutor in regard to the subject and having furnishedmost of the elements that informs Rorty's present conception of truth, has an especial part in this dissertation. The leading element on the reconstruction of this course was the question if Rorty manages to avoid what he himself calls "platonism" on philosophy and still develop a consistent conception of truth that justifies his belonging to the pragmatist tradition. With this aim, we approached in the first chapter the thought of James and Dewey in regard to truth and the critics and appropriations of both these conceptions made by Rorty. In the second chapter, we approached the conception of knowledge and truthexposed by Rorty in his most important work intending to stress not only the main points of what is needed for a secularized conception of inquiry, but also to point out the conception of truth internal to it. In the third chapter we approached his discussion with Davidson in regard to truth in order to clear the main points of Rorty's conception of truth and todemonstrate that, without the support given by some Davidsonian theses, Rorty's conception of truth wouldn't stand up. Finally, we believe we demonstrated that Rorty is able to provide a consistent conception of truth that is free of platonist suppositions and can still be considered as a pragmatist perspective.